Listeria Species Occurrence and Associated Risk Factors and Antibiogram of Listeria Monocytogenes in Milk and Milk Products in Ambo, Holeta, and Bako Towns, Oromia Regional State, Ethiopia - Bizunesh Mideksa Borena; Lemma Dilgasa; Endrias Zewdu Gebremedhin; Edilu Jorga Sarba; Lencho Megersa Marami; Kebede Abdisa Kelbesa; Nega Desalegn Tadese (Veterinary Medicine International)
A cross-sectional study was conducted to estimate the prevalence and associated risk factors of Listeria species and assess the antibiogram of Listeria monocytogenes (L. monocytogenes) isolated from milk and milk products from Holeta, Ambo, and Bako towns, Ethiopia. A total of 482 samples (384 milk, 35 cottage cheeses, 30 bulk tank milk, and 33 curdle milk) were collected using a systematic random sampling method and isolation and identification of Listeria species were done using standard microbiological techniques. An antimicrobial susceptibility test for L. monocytogenes was performed using the Kirby–Bauer disk diffusion technique. Descriptive statistics were used to summarize the prevalence of Listeria, while the Chi-square test and logistic regression were used to determine the association between the prevalence of Listeria and the risk factors and the magnitude of association, respectively. The overall isolation rate of Listeria species from milk and milk products was 7.67% (37/482; 95% confidence interval (CI): 5.46, 10.42). The highest prevalence of Listeria species (15.15%; 95% CI: 5.11–31.90) was detected in bulk tank milk and the lowest prevalence of Listeria species (6.67%; 95% CI: 0.82–22.07) and L. monocytogenes (0.00; 95% CI: 0.00–1.15) was found in curdled milk. The other species isolated were Listeria welshimeri 0.62% (3/482; 95% CI: 0.13–1.81), Listeria seeligeri 1.04% (5/482; 95% CI: 0.33–2.40), Listeria ivanovi 1.24%, (6/482; 95% CI: 0.45–2.68), and Listeria grayi 2.49% (12/482; 95% CI: 5.46–10.42). Univariable logistic regression showed that study town, herd size, farm size, number of lactating cows, and management system were the factors significantly associated with the isolation of Listeria species at farm level, while the intensive management system was the independent predictor at cow level in the multivariable model (adjusted odds ratio = 3.38, P=0.046). L. monocytogenes isolates showed the highest resistance against oxacillin (100%), amoxicillin (90.91%), and vancomycine (81.82%). L. monocytogenes showed a very high multidrug resistance (MDR) [81.82%]. In conclusion, the current study showed the widespread type of Listeria species MDR L. monocytogenes isolates in cow raw milk and milk products from Ambo, Holeta, and Bako towns, Oromia Regional State, Ethiopia.